(untitled) (Journal of the College of Education for Women, 2019)
Interval lies at rest in the speech; so as to improve to speak out, which is how Evaln Koran by other speech, called separators; for the secession of Alkalaman then, as the last verse separation between it and its aftermath in the Al-Jinn had a comma significant impact on the statement of the case of gin, as portrayed interval Gin and like the distraught after hearing of the KoranThis Sura carried various types of repetition represent wordy repeat itself and repeat some of the votes as well as the repeated sound of a thousand who remained in Sura breaks Bhaa also repeat the voice of the shredder breaksLinguistic sounds of Koranic breaks played a significant role in a statement carried by the linguistic meaning of these interludes, as she had broad implications on the wordyThe Qur’anic miracles renewed as soon as look at the voice shredder which unite in the verses breaks